2021
DOI: 10.3390/v13122536
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Ventilation, HEPA Air Cleaners, Universal Masking, and Physical Distancing for Reducing Exposure to Simulated Exhaled Aerosols in a Meeting Room

Abstract: There is strong evidence associating the indoor environment with transmission of SARS-CoV-2, the virus that causes COVID-19. SARS-CoV-2 can spread by exposure to droplets and very fine aerosol particles from respiratory fluids that are released by infected persons. Layered mitigation strategies, including but not limited to maintaining physical distancing, adequate ventilation, universal masking, avoiding overcrowding, and vaccination, have shown to be effective in reducing the spread of SARS-CoV-2 within the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
19
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Physical distancing has been shown to be important when individuals are facing each other less than 1.8 m apart indoors [ 19 , 20 ]. Beyond physical distance, ventilation in a room becomes the dominant contributor to aerosol dispersion and, therefore, personal exposure [ 21 , 22 ]. Increasing indoor ventilation by increasing outdoor and total airflow through heating, ventilation, and air conditioning (HVAC) systems, using more efficient central HVAC filters [ 23 ], opening windows to increase natural ventilation [ 24 ], and/or adding supplemental air filtration systems help reduce exposure [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Physical distancing has been shown to be important when individuals are facing each other less than 1.8 m apart indoors [ 19 , 20 ]. Beyond physical distance, ventilation in a room becomes the dominant contributor to aerosol dispersion and, therefore, personal exposure [ 21 , 22 ]. Increasing indoor ventilation by increasing outdoor and total airflow through heating, ventilation, and air conditioning (HVAC) systems, using more efficient central HVAC filters [ 23 ], opening windows to increase natural ventilation [ 24 ], and/or adding supplemental air filtration systems help reduce exposure [ 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, portable HEPA air cleaners can provide a rapidly deployable alternative to increasing effective ventilation rates where renovating existing HVAC systems is not immediately practical. In three studies using mechanical breathing simulators, the use of commercially available portable HEPA air cleaners that were sized to provide 5 air changes per hour (ACH) of filtered air led to a >50% reduction in exposure to simulated exhaled aerosols [ 21 , 31 , 32 ]. Another study using a calculation model found that the addition of portable HEPA filtration units sized to provide 5.4 ACH can help reduce transmission of SARS-CoV-2 [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, multi-occupation investigation into mitigation methods is currently limited. Modelling, simulation and observational studies of workplace COVID-19 prevention and control strategies indicate that layered packages of mitigation methods -including gradual return to in-person working, asymptomatic testing, reduction of contact, and using personal protective equipment (PPE)appear effective and more likely to reduce worker positivity compared to single measures (7)(8)(9)(10)(11)(12). However, studies thus far have tended to focus on single workplaces, and many sectors outside of health and social care settings are underrepresented in the current literature (9).…”
Section: Introductionmentioning
confidence: 99%
“…Tracer methods are currently used in indoor air quality investigations; these typically use tracer gases rather than aerosols. [19][20][21][22] For example, both ASHRAE and ASTM International have standardized test procedures. 23,24 While tracer gases are the most common approach for acquiring quantitative data on ventilation rates; however, it may not fully represent bioaerosol behavior.…”
Section: Introductionmentioning
confidence: 99%